Sample exercises for testing vocabulary skills in grade six - Esplana, Librada (Herrero) 1942- ([Quezon City s.n.], 1972)
This is part of a series of seminar papers which present sample exercises for testing vocabulary skills, from Grade 6 through fourth year high school. This particular paper covers testing vocabulary skills in Grade 6.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Vocabulary tests